Implementation of the MBKM Curriculum (Independent Learning Independent Campus) Towards the Islamic Religious Education Study Program at Higher College Level - Khairatunnimah. SM; Reni Puspita Sari; Arifatus Solihah (Yayasan Adra Karima Hubbi, 2024)
Background. Universities have so far implemented a credit learning system which is almost entirely dependent on classroom learning. This shows the low level of learning independence for students. Therefore, the idea of “Independent Learning Independent Campus” emerged, or